Factors associated with neutralizing antibody levels induced by two inactivated COVID-19 vaccines for 12 months after primary series vaccination - Wang, Fuzhen; Huang, Baoying; Lv, Huakun; Feng, Lizhong; Ren, Weihong; Wang, Xiaoqi; Tang, Lin; Liu, Qianqian; Wu, Dan; Zheng, Hui; An, Zhijie; Deng, Yao; et al. (Frontiers in Immunology, 2022)
Background: BBIBP-CorV and CoronaVac inactivated COVID-19 vaccines are widely-used, World Health Organization-emergency-listed vaccines. Understanding antibody level changes over time after vaccination is important for booster dose policies. We evaluated neutralizing antibody (nAb) titers and associated factors for the first 12 months after primary-series vaccination with BBIBP-CorV and CoronaVac. Methods: Our study consisted of a set of cross-sectional sero-surveys in Zhejiang and Shanxi provinces, China. In 2021, we enrolled 1,527 consenting 18-59-year-olds who received two doses of BBIBP-CorV or CoronaVac 1, 3, 6, 9, or 12 months earlier and obtained blood samples and demographic and medical data. We obtained 6-month convalescent sera from 62 individuals in Hebei province. Serum nAb titers were measured by standard micro-neutralization cytopathic effect assay in Vero cells with ancestral SARS-CoV-2 strain HB01. We used the first WHO International Standard (IS) for anti-SARS-CoV-2 immunoglobulin (NIBSC code 20/136) to standardized geometric mean concentrations (IU/mL) derived from the nAb geometric mean titers (GMT over 1:4 was considered seropositive). We analyzed nAb titer trends using Chi-square and factors related to nAb titers with logistic regression and linear models. Results: Numbers of subjects in each of the five month-groupings ranged from 100 to 200 for each vaccine and met group-specific target sample sizes. Seropositivity rates from BBIBP-CorV were 98.0% at 1 month and 53.5% at 12 months, and GMTs were 25.0 and 4.0. Respective seropositivity rates from CoronaVac were 90.0% and 62.5%, and GMTs were 20.2 and 4.1. One-, three-, six-, nine-, and twelve-month GMCs were 217.2, 84.1, 85.7, 44.6, and 10.9 IU/mL in BBIBP-CorV recipients and 195.7, 94.6, 51.7, 27.6, and 13.4 IU/mL in CoronaVac recipients. Six-month convalescent seropositivity was 95.2%; GMC was 108.9 IU/mL. Seropositivity and GMCs were associated with age, sex, and time since vaccination. Conclusions: Neutralizing Ab levels against ancestral SARS-CoV-2 from BBIBP-CorV or CoronaVac vaccination were similar and decreased with increasing time since vaccination; over half of 12-month post-vaccination subjects were seropositive. Seropositivity and GMCs from BBIBP-CorV and CoronaVac six and nine months after vaccination were similar to or slightly lower than in six-month convalescent sera. These real-world data suggest necessity of six-month booster doses.